Measuring Net Benefits in Business Combinations - Ugalde Binda, Nadia (2009)
Mergers and acquisitions grew an annual 20% between 1990 and 2000, with transactions that surpassed U.S. $1,000 trillions between 1998 and 2000 (Andre, 2004). For that reason, one could believe that they are creative sources of value for companies. However, a study at Business Week during 2002 indicates the contrary, 61% of these transactions destroy shareholders’ value (Andre, 2004). This research looks for relating transaction costs, resources and capacities theories to summarize incomes and costs of mergers and acquisitions’ processes. It systematizes net benefit’s calculation. Until now, the failures in the mergers have been measured by the absence of shareholders value’s increment, by later disinvestment, or using some isolated measures like demotivation in human resources, rotation, etc. Nevertheless, this research contributes integrating a model of valuation in businesses combination and its variables costs, incomes and net benefit in monetary and qualitative terms. The measures are important to feedback the later processes of combinations, to correct the undertaken ones, to manage synergies and to identify the sources of creation and destruction of value.